A Simple and Rapid Spectrophotometric Method for the Analysis of Sulfadimidine in Pharmaceutical Veterinary Dosage Forms - RAMI REDDY, N.; PRABHAVATHI, K.; CHAKRAVARTHY, I.E. (Asian Journal of Chemistry, 2010)
A new spectrophotometric method has been developed for the quantitative estimation of sulfadimidine in its pharmaceutical dosage forms. In this method the drug was reacted with sodium nitrite in acidic medium at 0-5°C temperature for diazotization. The . diazotised drug was treated with 1: 10 ammonia: water solution. A yellow colour was produced. The absorbance of the yellow colour solution was measured at 420 nm against reagent blank.